Parenting Patterns in the Qur'an (Analysis of the Story of Imran's Wife) - Minhatul Maula (Journal of Southeast Asian Islam and Society, 2024)
Parenting styles make a huge contribution to the social, emotional and intellectual competence of children. Of course this is a challenge for parents how to produce competent generations in their era. The Qur'an has a relevant offer for this, because its content is shalih li kulli Zaman wa Makan (Universal in every place and time) and most of the stories in the Qur'an have the concept of repetition for the future with different figures and times. This article will describe the upbringing that the Koran offers through the story of Imran's wife who has proven successful in educating Maryam. The Koran does not specifically talk about parenting, but conceptually these values are contained in the Koran. The author uses the method of conceptual thematic interpretation and in-depth analysis of language then contextualizes it with the present. The conclusion of this paper, among other things, is that prenatal and postnatal parenting greatly affect the growth and development of children, parents have aspired for the future of their children since they were in the womb and one of the parenting concepts that is quite unique is that the Koran invites parents to choose education. boarding schools for children because the education system adhered to by pesantren is able to produce a generation of rabbanis with a Qur'anic spirit